Intratextual fundamentalism and the desire for simple cognitive structure: the moderating effect of the ability to achieve cognitive structure - Muluk, Hamdi (Archive for the psychology of religion, 2010)
Religious fundamentalism has been suspected as a product of simple cognitive structuring. On the other hand, recent publications have shown that cognitive structure formation is not as simple as was previously thought. The concept of the Ability to Achieve Cognitive Structure (AACS) revealed that not everyone was able to form simple cognitive structure. This study employed a total of 187 Indonesian university students as participants. By the mean of Structural Equation Modeling, this study treated the desire for simple cognitive structure as a “new” latent variable and examined its relation with intratextual fundamentalism using AACS as moderator. The desire for simple structure was reflected by the Need for Cognitive Structure (NCS), the Dogmatism, and the RWA. The fundamentalism was reflected by the Intratextual Fundamentalism Scale (IFS). The result showed that fundamentalism, among other things, was a product of desire for simple cognitive structure. This study also showed that AACS moderated the relation in which high AACS would lead to higher fundamentalism while low AACS would not. Implications of the findings for social psychology and cross-cultural understanding of religious fundamentalism were discussed.